2021
DOI: 10.31926/but.fwiafe.2021.14.63.2.8
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effectiveness of Cocoa Butter (CB) and Cocoa Butter Alternatives (CBA) in Chocolate Manufacture

Abstract: This study aimed at (a) comparing the effectiveness of the use of Cocoa Butter (CB) and Cocoa Butter Alternatives (CBA) on food products and (b) measuring the effectiveness of the sub-groups of the Cocoa Butter Alternatives. In this study, the researchers used Structural Equation Modelling (SEM) with the Partial Least Square (PLS) approach. The analysis showed that (a) CB was more effective in the utilization than CBA and (b) after comparing sub-groups of the CBA examined in this study, Cocoa Butter Substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The study indicated that cocoa butter substitutes (CBSs) are more acceptable than cocoa butter replacers (CBRs) and cocoa butter equivalents (CBEs) in chocolate making among cocoa butter alternative (CBA) subgroups. The reasons that the use of CBRs and CBEs are not as preferable as CBSs in chocolate making has been studied and is stated in ▶ Table 2 [21,22].…”
Section: Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that cocoa butter substitutes (CBSs) are more acceptable than cocoa butter replacers (CBRs) and cocoa butter equivalents (CBEs) in chocolate making among cocoa butter alternative (CBA) subgroups. The reasons that the use of CBRs and CBEs are not as preferable as CBSs in chocolate making has been studied and is stated in ▶ Table 2 [21,22].…”
Section: Food Industrymentioning
confidence: 99%
“…Polymorphic transition in solid lipid nanoparticles (SLNs) depended on multiple factors and variables in the study. For instance, the uses of lipid(s) and emulsifiers generated particle size and the applied temperature during cooling and storage might exert an effect on the polymorphic transition in SLNs ▶ Table 2 Limitation in the use of cocoa butter replacers (CBRs) and cocoa butter equivalents (CBEs) in the production of chocolate [21,22].…”
Section: Pharmaceutical Industrymentioning
confidence: 99%